1996
DOI: 10.1002/jlb.59.5.716
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors from rat neutrophils responsible for cytotoxicity to isolated hepatocytes

Abstract: Activated polymorphonuclear neutrophils (PMNs) have been shown to be cytotoxic to rat hepatic parenchymal cells in vitro. This cytotoxicity could be observed without direct cell-cell contact, since the conditioned medium from PMNs activated with formyl-Met-Leu-Phe (fMLP) was effective in hepatocyte killing. To identify the toxic factor(s) released by PMNs, degranulation was induced by fMLP in PMNs pretreated with cytochalasin B. The contents released from the phagocytes were subjected to gel filtration on a Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…4) almost abolished hepatocellular injury suggested an interdependence of hemostasismediated hypoxia and PMNs in LPS/RAN-induced liver injury. Because toxic PMN proteases are important mediators of hepatocellular killing both in vitro and in vivo in other models of PMN-dependent liver injury (Ho et al, 1996;Ishii et al, 2002), we explored the potential for interaction between hypoxia and PMN elastase in HPC killing. Using isolated HPCs, preliminary experiments were conducted to identify a reduction in chamber O 2 concentration to which HPCs could be exposed without evidence of significant cytotoxicity, as evaluated by the release of ALT into culture medium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4) almost abolished hepatocellular injury suggested an interdependence of hemostasismediated hypoxia and PMNs in LPS/RAN-induced liver injury. Because toxic PMN proteases are important mediators of hepatocellular killing both in vitro and in vivo in other models of PMN-dependent liver injury (Ho et al, 1996;Ishii et al, 2002), we explored the potential for interaction between hypoxia and PMN elastase in HPC killing. Using isolated HPCs, preliminary experiments were conducted to identify a reduction in chamber O 2 concentration to which HPCs could be exposed without evidence of significant cytotoxicity, as evaluated by the release of ALT into culture medium.…”
Section: Resultsmentioning
confidence: 99%
“…Activated PMNs release several cytotoxic factors, including the proteases such as PMN elastase, which can kill rat HPCs in vitro (Ho et al, 1996). Few studies have examined the relationship between hypoxia and cellular sensitivity to toxic proteases.…”
Section: Hypoxia and Neutrophils In Lps/ran Liver Injury 1029mentioning
confidence: 99%
See 1 more Smart Citation
“…18 It has been shown that the neutrophil proteases elastase and cathepsin G are highly cytotoxic to hepatocytes in vitro. 19 Still another mechanism by which neutrophils may contribute to hepatic injury is through impedance and occlusion of hepatic sinusoids. Neutrophils must deform to pass through tissue capillaries, including hepatic sinusoids.…”
Section: Neutralization Of Kc or Mip-2 Attenuates Hepatic Neutrophilmentioning
confidence: 99%
“…[81][82][83] Here, neutrophils can generate tissue injury through the liberation of toxic oxygen radicals and proteolytic enzymes, such as elastase and cathepsin G, which are highly cytotoxic to hepatocytes. 84 Also, the adherence of neutrophils to the endothelium leads to an impaired microcirculation, which results in the plugging of capillaries, the occlusion of hepatic sinusoids, and an aggravation of the hepatic injury and dysfunction. 82,83,85 The important role of neutrophils in the development of postresection hepatic injury was clearly shown by Pagetti et al, 86 who showed that neutrophil depletion before injury greatly attenuated liver dysfunction.…”
Section: Bpi In Liver Surgerymentioning
confidence: 99%